Circulating microRNAs as Novel Biomarkers for Atherosclerosis - YILMAZ, SEDA GULEC (In Vivo, 2018)
Background/Aim: In this study, we determined the expression of selected circulating microRNAs (miRNA) and their potential roles as biomarkers in patients with atherosclerosis and a control group. Materials and Methods: In order to obtain insight into miRNA expression levels in atherosclerosis, we analyzed miRNA expression levels by real-time polymerase chain reaction (RT-PCR) in case (n=89) and healthy control (n=93) groups. Receiver operating characteristic curve analysis was performed to assess the diagnostic capability of miRNAs. Results: miRNA221 and miRNA221 expression levels were significantly lower in patients than controls (p=0.011 and p=0.004, respectively). Receiver operator curve analysis demonstrated that expression levels of miRNA221 [area under curve (AUC)=0.623, p=0.0086) and miRNA222 (AUC=0.654, p=0.0006) were significantly different between groups. There were positive correlations between miRNA122a and triglyceride (p=0.046) and very-low-density lipoprotein (p=0.029) levels. Conclusion: miRNA221 and miRNA222 could be convenient biomarkers for diagnosis of atherosclerosis.